Hodographic study of non-Newtonian MHD aligned steady plane fluid flows - P. V. Nguyen; O. P. Chandna (International Journal of Mathematics and Mathematical Sciences)
A study is made of non-Newtonian HHD aligned steady plane fluid flows to find exact solutions for various flow configurations. The equations of motion have been transformed to the hodograph plane. A Legendre-transform function is used to recast the equations in the hodograph plane in terms of this transform function. Solutions for various flow configurations are obtained. Applications are investigated for the fluids of finite and infinite electrical conductivity bringing out the similarities and contrasts in the solutions of these types of fluids.